Novel LRP/LR induced stem-cell-like cells to aid wound healing and regeneration - Chigumba, Stephanie (My University, 2019)
The 37/67kDa Laminin Receptor (LRP/LR) LR is a multifunctional cell surface receptor that maintains several survival processes. It has recently been found that there is a direct relationship between LRP/LR and the stem cell marker telomerase. Studies have shown that overexpression of FLAG tagged LRP increases hTERT levels and telomerase activity. Telomerase is a reverse transcriptase enzyme found in actively dividing cells whose core function involves telomere maintenance and elongation. The rate limiting component of telomerase, hTERT, is also often upregulated in rapidly dividing cells to aid stem cell renewal and cell survival and its ectopic expression can induce epithelial to mesenchymal transition (EMT) resulting in stem cell like characteristics. In adults, the primary role of stem cells is to repair and regenerate tissue. Hence, this study aims to determine whether overexpressing LRP::FLAG and the subsequent increase in hTERT levels induces stem-cell-like characteristics and promotes repair and regeneration in MRC5 lung fibroblasts and HEK293 embryonic kidney cells. Cells were stably transfected with the pCIneo-moLRP-FLAG plasmid in order to induce LRP::FLAG overexpression. Post-transfection, an increase in hTERT and phospho-TERT protein levels was observed in both cell lines which is crucial in maintaining the self-renewal capacity of stem cells. Additionally, an increase in the levels of pluripotency stem cell markers involved in cell reprogramming and alkaline phosphatase activity was also observed for HEK293 after transfection. However, in MRC5 cells there was an insufficient expression of reprogramming factors but, a Cadherin switch indicative of EMT. Moreover, HEK293 cells overexpressing LRP::FLAG showed no significant changes in the protein levels of the pro-inflammatory cytokine NF-κB1 and an increase in the anti-inflammatory cytokine TGFβ1 which modulates wound healing. In turn, it led to an increase in the adhesion and migratory capacity of HEK293 cells. This data suggests that overexpressing LRP::FLAG induces EMT similar to that observed during induced cell reprogramming and could possibly promote wound healing by upregulating TERT and TGFβ1 protein levels resulting in stem-cell-like characteristics.
A thesis submitted to the Faculty of Science in fulfilment of the requirement for the degree of Master of Science, University of the Witwatersrand, Johannesburg, 2019
Keywords: Cancer; Cancer cells; Small interfering RNA